A PEN INJECTOR FOR SELF-ADMINISTRATION OF FOLLITROPIN ALPHA SOLUTION WITH A MINIMAL DOSE INCREMENT OF 5 IU - A. B. Podkorytov; O. V. Zhilyaev; M. A. Polzikov (Акушерство, гинекология и репродукция, 2018)
To date, self administrations of recombinant human follicle-stimulating hormone (rhFSH) are carried out using pen injectors with minimal dose increments of 8.33 IU or 12.5 IU (IU – international units of activity). To ensure the accuracy of dose titration and to minimize the dose adjustments during the treatment, new pen injectors are needed. Those would provide for the self administration of rhFSH in a wide range of doses and with a dose increment less than the existing fractional values. Aim: to develop a pre-filled, multi-dose pen injector for rhFSH solution with a 5 IU dose increment and a dose setting from 0 to 300 IU.Materials and methods. Dispensed volumes containing the minimal dose of 5 IU were measured gravimetrically.Results. After testing 48 pen injectors the estimated minimal dose of 5 IU (0.0083 ml of the solution) produced the following results: the mean value of the dispensed volume was 0.0081 ml, the mean deviation was ± 0.0006 ml (or ± 0.36 IU). The results are in consistence with the ISO 11608-1:2014(E) requirements of dose accuracy for the minimal dose setting in commercial injectors.Conclusion. We have developed a pen injector for rhFSH administration with a dose setting from 0 to 300 IU and with a minimal increment of dose adjustment of 5 IU. The individual approach to the dose selection/adjustment with a minimal increment of 5 IU may help achieving a highly accurate administration of rhFSH for the controlled ovarian hyperstimulation and for the induced-ovulation protocols with growth activation of 1-2 follicles.